Analisis Komparatif Tingkat Aktivitas Fisik Mahasiswa Gen Z Berdasarkan Kepadatan Penduduk - Syahvira Syahvira; Helmy Firmansyah; Mudjihartono Mudjihartono; Yudy Hendrayana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze and compare the physical activity levels of Generation Z university students based on the population density of their residential areas, specifically between high-density and low-density regions. A quantitative approach with a comparative survey method was employed. The sample included 157 active university students aged 16–27 years, with 87 from campuses in high-density areas (Bandung City) and 70 from low-density areas (Sumedang Regency). Physical activity levels were measured using the short version of International Physical Activity Questionnaire (IPAQ. Data were analyzed using the Kolmogorov-Smirnov normality test, followed by the Mann-Whitney non-parametric test due to the non-normal distribution of data. The results showed that the average physical activity level of students in high-density areas was 3600 MET-minutes/week, slightly higher than those in low-density areas with an average of 3585.143 MET-minutes/week. However, the Mann-Whitney test revealed that the difference was not statistically significant (significance value = 0.795 > 0.05). Thus, it can be concluded that population density does not significantly impact the physical activity levels of Generation Z students. Other factors such as motivation, lifestyle, and access to facilities may play a substantial role. Keywords: Physical activity, population density, university students, Generation Z, IPAQ